Laporan Kasus: Pyometra Pada Anjing Ras Labrador : Case Report: Pyometra in Labrador Dog - Anna Zukiaturrahmah; Juliadi Ramadhan; Ario Ridho Gelagar; Usma Aulia (Fakultas Pertanian Universitas Majalengka, 2023)
Pyometra is one of the important causes of infertility in female animals, including dogs. Pyometra is accumulation of pus in the uterus caused by bacteria that are normally in the uterus but in certain circumstances become pathogens due to hormonal influences. This case report aims to determine the etiology, clinical symptoms, diagnosis, prognosis and treatment of pyometra disease in dogs. The examination method that is carried out is physical examination and investigations, hematology, blood chemistry, and ultrasound. Based on a physical examination in the form of inspection of the lesions on the vulva and abdominal enlargement. Palpation of the mesogastrium and hypogastrium is the presence of abdominal tension. Hematologic results show leukocytosis, neutrophilia, and hyperchromic normocytic anemia. Blood chemistry examination results showed azotemia, increased AST, ALP and GGT. Ultrasound examination results show that an anechoic period is accumulation of uterine fluid and thickening of the uterine wall. The diagnosis of this case is pyometra. The therapy performed is ovariohisterectomy surgery. After surgery animals were given medicines including Cephalexine, Meloxicam, Ursodeoxycholic acid, and S-adenosylmethionine (SAMe). On the sixth day the animal surgery post improves again and is allowed to be taken home.